Pengaruh bahan ajar bermuatan literasi saintifik dan HOTS dalam model pembelajaran penemuan materi fluida terhadap hasil belajar siswa kelas XI SMAN 10 Padang - Annisa Lendri; Asrizal Asrizal (Universitas Negeri Padang, 2019)
In the 21st century, education should be able to produce the graduates with holistic and balanced competencies. For this reason, the Indonesian government has created a school literacy program to improve the learning outcomes of students. But the real condition indicated that physics learning with literacy was still limited in reading skill. The solution to this problem was to apply the learning material with scientific literacy and HOTS in the discovery learning model. The purpose of the research was to investigate the effect of learning material with scientific literacy and HOTS in the discovery learning model of fluid material on the learning outcomes of grade XI students in SMAN 10 Padang. This type of research was quasi-experimental research. The research design was Randomized Control-Group Only Design. The research population was all students of grade XI of SMAN 10 Padang. The sampling techniques in this research were purposive sampling and cluster random sampling. The sample of the research was the grade XI MIA 5 as the experimental group and the grade XI MIA 2 as the control group. The research instruments were a written test to assess knowledge, a performance assessment sheet for assessing skills, and an observation sheet to assess the attitudes of students. The research data were analyzed by using descriptive statistics, normality and homogeneity test, and comparison test of two means. Based on the result of data analysis, it can be stated that there is a significant difference the learning outcomes between students who use the learning material with scientific literacy and HOTS and students who didn’t it in the discovery learning model of fluid material at SMAN 10 Padang with a confidence level of 95%. Therefore, the use of learning material with scientific literacy and HOTS in the discovery learning model of fluid material has given a significant effect on learning outcomes of students for three aspects, namely knowledge, skills and attitudes.